(untitled) (International Journal of Engineering Management Science, 2025)
Cross-cultural management please key role in a globalised business environment where companies work in a variety of cultural context. This article analyses the discoveries and developments in international companies play analysing challenges and openings in the social administration. It deals with the complexity of navigation of cultural differences, the structure of effective intercultural teams, and implementation of strategies that promote cross cultural understanding and collaboration. This research is based on modern real-world research and examples and provides valuable perspective for business success. A company that wants to prosper in a multicultural environment. Through an analysis of innovative approaches and best practices, this paper provides comprehensive overview of developing regions of cross cultural management and provides important global insights.